Guinness World records 2018 - "NA" (Guinness World Records Limited , London, 2017)
Guinness World Records 2018 is bursting with all-new records on topics as diverse as black holes, domes, owls, and killer plants. And of course all your favorite record categories are updated, such as the world's new tallest dog! Plus, want to be a record-breaker? There are exciting challenges you can try at home
Keywords: World record